"To Feel the Drumming Earth Come Upward": Indigenizing the American Studies Discipline, Field, Movement - Clark, D.Anthony Tyeeme; Yetman, Norman R. (American Studies, 2005)
"To Feel the Drumming Earth Come Upward": Indigenizing the American Studies Discipline, Field, Movement